Linear cooling process of layered ternary positive electrode material

By using a linear cooling process of layered ternary positive electrode material in the production of battery positive electrode materials, the problem of fast cooling speed after sintering leads to instability of the material is solved, and the stability and electrochemical properties of the material are significantly improved.

CN119797447APending Publication Date: 2025-04-11CENT SOUTH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510008610.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing battery positive electrode material production process is fast during cooling after sintering, resulting in unstable material structure and affecting electrochemical performance.

Method used

The linear cooling process of layered ternary positive electrode material is adopted. The material after high temperature calcination is linearly cooled from high temperature, and the temperature drops below 150℃, and the cooling rate is controlled to be 1-20℃/min.

Benefits of technology

The lithium-nickel mixture of the material is reduced, and the stability and electrochemical properties of the material structure are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119797447A_ABST
    Figure CN119797447A_ABST
Patent Text Reader

Abstract

The invention relates to the field of battery materials, and discloses a linear cooling process of a layered ternary positive electrode material, which comprises the following steps: step 1, mixing a NixCoyMnz (OH) 2 hydroxide precursor with a lithium source through a high-efficiency mixer, and then carrying out high-temperature calcination; and 2, carrying out linear cooling on the roasted material in the step 1 from a high temperature, and taking out the material when the temperature is reduced to 150 DEG C or below, so as to obtain the LiNixCoyMnzO2 layered ternary positive electrode material, wherein x is larger than or equal to 0.5 and smaller than or equal to 1, y is larger than or equal to 0 and smaller than or equal to 0.5, z is larger than or equal to 0 and smaller than or equal to 0.5, and x + y + z = 1. According to the process design, linear cooling is conducted after high-temperature calcination is finished, the cooling rate is 1-20 DEG C / min, a sample is taken out until the temperature is lowered to 150 DEG C or below, the lithium-nickel mixed arrangement degree of the material prepared through linear cooling is low, and the structural stability and the electrochemical performance of the material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of battery materials, and in particular to a linear cooling process for layered ternary positive electrode materials. Background Art

[0002] At present, the focus of the production process of battery positive electrode materials is mostly concentrated on the material preparation stage, and doping elements are introduced when preparing the precursor or when mixing lithium. After the positive electrode material is prepared by sintering the mixed lithium, it is mixed with the coating and coated on the surface of the positive electrode material. Through these methods, the material is modified by doping and coating to improve the stability of the positive electrode material, and less attention is paid to the cooling rate in the material cooling stage, thereby ignoring that the cooling rate is also one of the important factors affecting the stability of the material.

[0003] According to the process design, during the production of lithium battery positive electrode materials, the positive electrode materials need to be fed into the sagger using a sintering furnace feeder, and the materials are shaken and leveled before being sent into the sintering furnace for sintering. After sintering, the sagger is taken out of the sintering furnace for cooling. After cooling, the positive electrode materials are crushed and sieved.

[0004] In the sintering process, in order to save costs and increase production, short sintering cycles and high loading amounts have always been the direction of process research; but at the same time, short-cycle processes will lead to a shortened cooling period after sintering. While reducing production capacity, if a reasonable cooling method can be adopted in the cooling section, it will be helpful for industrial production. At the same time, in the process of controlling the cooling rate of the layered material, the crystal structure will not produce a large amount of lattice distortion or dislocation due to natural cooling, thereby improving the orderliness of the material lattice structure. For this reason, this application proposes a linear cooling process for layered ternary positive electrode materials. Summary of the invention

[0005] The purpose of the present invention is to provide a linear cooling process for layered ternary positive electrode materials to solve the problems raised in the above background technology.

[0006] To achieve the above object, the present invention provides the following technical solution: a linear cooling process of a layered ternary cathode material, comprising the following steps:

[0007] Step 1: Ni x Co y Mn z The (OH)2 hydroxide precursor is mixed with a lithium source by a high-efficiency mixer and then calcined at high temperature;

[0008] Step 2, the material calcined in step 1 is linearly cooled from high temperature, and the temperature is lowered to below 150° C. to obtain the LiNi x Co y Mnz O2 layered ternary cathode material;

[0009] Among them, 0.5≤x≤1, 0≤y≤0.5, 0≤z≤0.5, x+y+z=1.

[0010] Preferably, the lithium source in step 1 is selected from one or a combination of lithium hydroxide, lithium carbonate, lithium acetate and lithium nitrate.

[0011] Preferably, the high temperature calcination and sintering process in step 2 is specifically calcining at 500°C for 4-6h and calcining at 720-950°C for 12h.

[0012] Preferably, the linear cooling rate in step 2 is 1-20°C / min.

[0013] Preferably, the operation process of step 1 and step 2 is performed in an atmosphere furnace.

[0014] Compared with the prior art, the present invention has the following beneficial effects:

[0015] The process method of the present invention performs linear cooling after high-temperature calcination, with a cooling rate of 1-20°C / min, until the sample is cooled to below 150°C and taken out. The material obtained by linear cooling has a low degree of lithium-nickel mixing, and the material structure stability and electrochemical performance are improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 It is a process flow chart of the present invention;

[0017] Figure 2 is a temperature-time relationship curve of Examples 3, 4, 5, 6 of the present invention and Comparative Example 2;

[0018] Figure 3 1 is the XRD diagram of Examples 1 and 2 of the present invention and Comparative Example 1;

[0019] Figure 4 is the XRD diagram of Examples 3, 4, 5, 6 of the present invention and Comparative Example 2;

[0020] Figure 5 is the XRD diagram of Examples 7 and 8 of the present invention and Comparative Example 3;

[0021] Figure 6 1 and 2 are XRD diagrams of Examples 9 and 10 of the present invention and Comparative Example 4. DETAILED DESCRIPTION

[0022] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] See also Figure 1 This is a process flow chart of the present invention, in which a linear cooling process of a layered ternary positive electrode material is shown, comprising the following steps:

[0024] Step 1: Ni x Co y Mn z The (OH)2 hydroxide precursor is mixed with a lithium source by a high-efficiency mixer and then calcined at high temperature;

[0025] Step 2, the material calcined in step 1 is linearly cooled from high temperature, and the temperature is lowered to below 150° C. to obtain the LiNi x Co y Mn z O2 layered ternary cathode material;

[0026] Among them, 0.5≤x≤1, 0≤y≤0.5, 0≤z≤0.5, x+y+z=1.

[0027] Example 1

[0028] In terms of molar ratio, LiOH and Ni 0.8 Co 0.1 Mn 0.1 The metal ion ratio of (OH)2 precursor material is Li: (Ni+Co+Mn) = 1.04:1. Weigh an appropriate amount of Ni 0.8 Co 0.1 Mn 0.1 (OH)2 and LiOH, the resulting Ni 0.8 Co 0.1 Mn 0.1 The (OH)2 precursor material and LiOH were uniformly mixed in a high-efficiency mixer for 0.5 h; two-stage sintering was performed in an oxygen atmosphere, calcined at 500°C for 4-6 h and 720-780°C for 12 h. After calcination, the sample was cooled to 150°C at a cooling rate of 3°C / min to obtain the positive electrode material LiNi 0.8 Co 0.1 Mn 0.1 O2.

[0029] The positive electrode material LiNi 0.8 Co 0.1 Mn0.1 O2 was tested by XRD. After refining the test results, the lithium-nickel mixed ratio of the material was 2.53%. 0.8 Co 0.1 Mn 0.1 O2 was assembled into a 2025 button battery with a charge and discharge voltage range of 2.8-4.3V. After 100 charge and discharge cycles at 1C, the capacity retention rate was 87.32%.

[0030] Example 2

[0031] In terms of molar ratio, LiOH and Ni 0.8 Co 0.1 Mn 0.1 The metal ion ratio of (OH)2 precursor material is Li: (Ni+Co+Mn) = 1.04:1. Weigh an appropriate amount of Ni 0.8 Co 0.1 Mn 0.1 (OH)2 and LiOH, the resulting Ni 0.8 Co 0.1 Mn 0.1 The (OH)2 precursor material and LiOH were uniformly mixed in a high-efficiency mixer for 0.5 h; two-stage sintering was performed in an oxygen atmosphere, calcined at 500°C for 4-6 h and 720-780°C for 12 h. After calcination, the sample was cooled to 150°C at a cooling rate of 10°C / min to obtain the positive electrode material LiNi 0.8 Co 0.1 Mn 0.1 O2.

[0032] The positive electrode material LiNi 0.8 Co 0.1 Mn 0.1 O2 was tested by XRD. After refining the test results, the lithium-nickel mixed ratio of the material was 2.82%. 0.8 Co 0.1 Mn 0.1 O2 was assembled into a 2025 button battery with a charge and discharge voltage range of 2.8-4.3V. After 100 charge and discharge cycles at 1C, the capacity retention rate was 87.05%.

[0033] Example 3

[0034] In terms of molar ratio, Li2CO3 and Ni 0.75 Mn 0.25 The metal ion ratio of (OH)2 precursor material is Li: (Ni+Mn) = 1.04:1. Weigh an appropriate amount of Ni 0.75 Mn 0.25 (OH)2 and Li2CO3, The obtained Ni 0.75 Mn 0.25 The (OH)2 precursor material and Li2CO3 were uniformly mixed in a high-efficiency mixer for 0.5 h; two-stage sintering was performed in an oxygen atmosphere, calcined at 500°C for 4-6 h and 815°C for 12 h. After calcination, the sample was cooled to 150°C at a cooling rate of 1°C / min to obtain the positive electrode material LiNi 0.75 Mn 0.25 O2.

[0035] The positive electrode material LiNi 0.75 Mn 0.25 O2 was tested by XRD. After refining the test results, the lithium-nickel mixed ratio of the material was 3.50%. 0.75 Mn 0.25 O2 was assembled into a 2025 button battery with a charge and discharge voltage range of 2.8-4.3V. After 100 charge and discharge cycles at 1C, the capacity retention rate was 82.43%.

[0036] Example 4

[0037] In terms of molar ratio, Li2CO3 and Ni 0.75 Mn 0.25 The metal ion ratio of (OH)2 precursor material is Li: (Ni+Mn) = 1.06:1. Weigh an appropriate amount of Ni 0.75 Mn 0.25 (OH)2 and Li2CO3, the resulting Ni 0.75 Mn 0.25 The (OH)2 precursor material and Li2CO3 were uniformly mixed in a high-efficiency mixer for 0.5 h; two-stage sintering was performed in an oxygen atmosphere, calcined at 500°C for 4-6 h and 815°C for 12 h. After calcination, the sample was cooled to 150°C at a cooling rate of 3°C / min to obtain the positive electrode material LiNi 0.75 Mn 0.25 O2.

[0038] The positive electrode material LiNi 0.75 Mn 0.25 O2 was tested by XRD. After refining the test results, the lithium-nickel mixed ratio of the material was 2.43%. 0.75 Mn 0.25 O2 was assembled into a 2025 button battery with a charge and discharge voltage range of 2.8-4.3V. After 100 charge and discharge cycles at 1C, the capacity retention rate was 88.17%.

[0039] Example 5

[0040] In terms of molar ratio, Li2CO3 and Ni 0.75 Mn 0.25 The metal ion ratio of (OH)2 precursor material is Li: (Ni+Mn) = 1.06:1. Weigh an appropriate amount of Ni 0.75 Mn 0.25 (OH)2 and Li2CO3, the resulting Ni 0.75 Mn 0.25 The (OH)2 precursor material and Li2CO3 were uniformly mixed in a high-efficiency mixer for 0.5 h; two-stage sintering was performed in an oxygen atmosphere, calcined at 500°C for 4-6 h and 815°C for 12 h. After calcination, the sample was cooled to 150°C at a cooling rate of 10°C / min to obtain the positive electrode material LiNi 0.75 Mn 0.25 O2.

[0041] The positive electrode material LiNi 0.75 Mn 0.25 O2 was tested by XRD. After refining the test results, the lithium-nickel mixed ratio of the material was 2.83%. 0.75 Mn 0.25 O2 was assembled into a 2025 button battery with a charge and discharge voltage range of 2.8-4.3V. After 100 charge and discharge cycles at 1C, the capacity retention rate was 87.14%.

[0042] Example 6

[0043] In terms of molar ratio, Li2CO3 and Ni 0.75 Mn 0.25 The metal ion ratio of (OH)2 precursor material is Li: (Ni+Mn) = 1.06:1. Weigh an appropriate amount of Ni 0.75 Mn 0.25 (OH)2 and Li2CO3, the resulting Ni 0.75 Mn 0.25 The (OH)2 precursor material and Li2CO3 were uniformly mixed in a high-efficiency mixer for 0.5 h; two-stage sintering was performed under an oxygen atmosphere, calcined at 500°C for 4-6 h and 815°C for 12 h. After the calcination, the material was immediately taken out and quickly cooled to 150°C to obtain the positive electrode material LiNi 0.75 Mn 0.25 O2.

[0044] The positive electrode material LiNi 0.75 Mn 0.25 O2 was tested by XRD. After refining the test results, the lithium-nickel mixed ratio of the material was 4.71%. 0.75 Mn 0.25O2 was assembled into a 2025 button battery with a charge and discharge voltage range of 2.8-4.3V. After 100 charge and discharge cycles at 1C, the capacity retention rate was 82.05%.

[0045] Example 7

[0046] In terms of molar ratio, Li2CO3 and Ni 0.6 Co 0.2 Mn 0.2 The metal ion ratio of (OH)2 precursor material is Li: (Ni+Co+Mn) = 1.04:1. Weigh an appropriate amount of Ni 0.6 Co 0.2 Mn 0.2 (OH)2 and Li2CO3, the resulting Ni 0.6 Co 0.2 Mn 0.2 The (OH)2 precursor material and Li2CO3 were uniformly mixed in a high-efficiency mixer for 0.5 h; two-stage sintering was performed in an oxygen atmosphere, calcined at 500°C for 4-6 h and 820-880°C for 12 h. After calcination, the sample was cooled to 150°C at a cooling rate of 3°C / min to obtain the positive electrode material LiNi 0.6 Co 0.2 Mn 0.2 O2.

[0047] The positive electrode material LiNi 0.6 Co 0.2 Mn 0.2 O2 was tested by XRD. After refining the test results, the lithium-nickel mixed ratio of the material was 2.05%. 0.6 Co 0.2 Mn 0.2 O2 was assembled into a 2025 button battery with a charge and discharge voltage range of 2.8-4.3V. After 100 charge and discharge cycles at 1C, the capacity retention rate was 87.76%.

[0048] Example 8

[0049] In terms of molar ratio, Li2CO3 and Ni 0.6 Co 0.2 Mn 0.2 The metal ion ratio of (OH)2 precursor material is Li: (Ni+Co+Mn) = 1.04:1. Weigh an appropriate amount of Ni 0.6 Co 0.2 Mn 0.2 (OH)2 and Li2CO3, the resulting Ni 0.6 Co 0.2 Mn 0.2The (OH)2 precursor material and Li2CO3 were uniformly mixed in a high-efficiency mixer for 0.5 h; two-stage sintering was performed in an oxygen atmosphere, calcined at 500°C for 4-6 h and 820-880°C for 12 h. After calcination, the sample was cooled to 150°C at a cooling rate of 10°C / min to obtain the positive electrode material LiNi 0.6 Co 0.2 Mn 0.2 O2.

[0050] The positive electrode material LiNi 0.6 Co 0.2 Mn 0.2 O2 was tested by XRD. After refining the test results, the lithium-nickel mixed ratio of the material was 2.05%. 0.6 Co 0.2 Mn 0.2 O2 was assembled into a 2025 button battery with a charge and discharge voltage range of 2.8-4.3V. After 100 charge and discharge cycles at 1C, the capacity retention rate was 87.76%.

[0051] Example 9

[0052] In terms of molar ratio, Li2CO3 and Ni 0.5 Co 0.2 Mn 0.3 The metal ion ratio of (OH)2 precursor material is Li: (Ni+Co+Mn) = 1.04:1. Weigh an appropriate amount of Ni 0.5 Co 0.2 Mn 0.3 (OH)2 and Li2CO3, the resulting Ni 0.5 Co 0.2 Mn 0.3 The (OH)2 precursor material and Li2CO3 were uniformly mixed in a high-efficiency mixer for 0.5 h; two-stage sintering was performed in an oxygen atmosphere, calcined at 500°C for 4-6 h and 880-950°C for 12 h. After calcination, the sample was cooled to 150°C at a cooling rate of 3°C / min to obtain the positive electrode material LiNi 0.5 Co 0.2 Mn 0.3 O2.

[0053] The positive electrode material LiNi 0.5 Co 0.2 Mn 0.3 O2 was tested by XRD. After refining the test results, the lithium-nickel mixed ratio of the material was 2.17%. 0.5 Co 0.2 Mn 0.3O2 was assembled into a 2025 button battery with a charge and discharge voltage range of 2.8-4.3V. After 100 charge and discharge cycles at 1C, the capacity retention rate was 90.36%.

[0054] Example 10

[0055] In terms of molar ratio, Li2CO3 and Ni 0.5 Co 0.2 Mn 0.3 The metal ion ratio of (OH)2 precursor material is Li: (Ni+Co+Mn) = 1.04:1. Weigh an appropriate amount of Ni 0.5 Co 0.2 Mn 0.3 (OH)2 and Li2CO3, the resulting Ni 0.5 Co 0.2 Mn 0.3 The (OH)2 precursor material and Li2CO3 were uniformly mixed in a high-efficiency mixer for 0.5 h; two-stage sintering was performed in an oxygen atmosphere, calcined at 500°C for 4-6 h and 880-950°C for 12 h. After calcination, the sample was cooled to 150°C at a cooling rate of 10°C / min to obtain the positive electrode material LiNi 0.5 Co 0.2 Mn 0.3 O2.

[0056] The positive electrode material LiNi 0.5 Co 0.2 Mn 0.3 O2 was tested by XRD. After refining the test results, the lithium-nickel mixed ratio of the material was 2.25%. 0.5 Co 0.2 Mn 0.3 O2 was assembled into a 2025 button battery with a charge and discharge voltage range of 2.8-4.3V. After 100 charge and discharge cycles at 1C, the capacity retention rate was 90.01%.

[0057] Comparative Example 1

[0058] In terms of molar ratio, LiOH and Ni 0.8 Co 0.1 Mn 0.1 The metal ion ratio of (OH)2 precursor material is Li: (Ni+Co+Mn) = 1.04:1. Weigh an appropriate amount of Ni 0.8 Co 0.1 Mn 0.1 (OH)2 and LiOH, the resulting Ni 0.8 Co 0.1 Mn 0.1The (OH)2 precursor material and LiOH were uniformly mixed in a high-efficiency mixer for 0.5 h; two-stage sintering was performed under an oxygen atmosphere, calcined at 500°C for 4-6 h, calcined at 720-780°C for 12 h, and naturally cooled to 150°C to take out the sample to obtain the positive electrode material LiNi 0.8 Co 0.1 Mn 0.1 O2.

[0059] The positive electrode material LiNi 0.8 Co 0.1 Mn 0.1 O2 was tested by XRD. After refining the test results, the lithium-nickel mixed ratio of the material was 4.23%. 0.8 Co 0.1 Mn 0.1 O2 was assembled into a 2025 button battery with a charge and discharge voltage range of 2.8-4.3V. After 100 charge and discharge cycles at 1C, the capacity retention rate was 85.30%.

[0060] Comparative Example 2

[0061] In terms of molar ratio, Li2CO3 and Ni 0.75 Mn 0.25 The metal ion ratio of (OH)2 precursor material is Li: (Ni+Mn) = 1.04:1. Weigh an appropriate amount of Ni 0.75 Mn 0.25 (OH)2 and Li2CO3, the resulting Ni 0.75 Mn 0.25 The (OH)2 precursor material and Li2CO3 were uniformly mixed in a high-efficiency mixer for 0.5 h; two-stage sintering was performed under an oxygen atmosphere, calcined at 500°C for 4-6 h, calcined at 815°C for 12 h, and naturally cooled to 150°C to take out the sample to obtain the positive electrode material LiNi 0.75 Mn 0.25 O2.

[0062] The positive electrode material LiNi 0.75 Mn 0.25 O2 was tested by XRD. After refining the test results, the lithium-nickel mixed ratio of the material was 4.65%. 0.75 Mn 0.25 O2 was assembled into a 2025 button battery with a charge and discharge voltage range of 2.8-4.3V. After 100 charge and discharge cycles at 1C, the capacity retention rate was 80.62%.

[0063] Comparative Example 3

[0064] In terms of molar ratio, Li2CO3 and Ni 0.6Co 0.2 Mn 0.2 The metal ion ratio of (OH)2 precursor material is Li: (Ni+Co+Mn) = 1.04:1. Weigh an appropriate amount of Ni 0.6 Co 0.2 Mn 0.2 (OH)2 and Li2CO3, the resulting Ni 0.6 Co 0.2 Mn 0.2 The (OH)2 precursor material and Li2CO3 are uniformly mixed in a high-efficiency mixer for 0.5 h; two-stage sintering is performed under an oxygen atmosphere, calcined at 500°C for 4-6 h, calcined at 820-880°C for 12 h, and naturally cooled to 150°C to take out the sample to obtain the positive electrode material LiNi 0.6 Co 0.2 Mn 0.2 O2.

[0065] The positive electrode material LiNi 0.6 Co 0.2 Mn 0.2 O2 was tested by XRD. After refining the test results, the lithium-nickel mixed ratio of the material was 4.05%. 0.6 Co 0.2 Mn 0.2 O2 was assembled into a 2025 button battery with a charge and discharge voltage range of 2.8-4.3V. After 100 charge and discharge cycles at 1C, the capacity retention rate was 86.34%.

[0066] Comparative Example 4

[0067] In terms of molar ratio, Li2CO3 and Ni 0.5 Co 0.2 Mn 0.3 The metal ion ratio of (OH)2 precursor material is Li: (Ni+Co+Mn) = 1.04:1. Weigh an appropriate amount of Ni 0.5 Co 0.2 Mn 0.3 (OH)2 and Li2CO3, the resulting Ni 0.5 Co 0.2 Mn 0.3 The (OH)2 precursor material and Li2CO3 are uniformly mixed in a high-efficiency mixer for 0.5 h; two-stage sintering is performed under an oxygen atmosphere, calcined at 500°C for 4-6 h, calcined at 880-950°C for 12 h, and naturally cooled to 150°C to take out the sample to obtain the positive electrode material LiNi 0.5 Co 0.2 Mn 0.3 O2.

[0068] The positive electrode material LiNi 0.5 Co 0.2 Mn 0.3 O2 was tested by XRD. After refining the test results, the lithium-nickel mixed ratio of the material was 3.96%. 0.5 Co 0.2 Mn 0.3 O2 was assembled into a 2025 button battery with a charge and discharge voltage range of 2.8-4.3V. After 100 charge and discharge cycles at 1C, the capacity retention rate was 88.80%.

[0069] The electrochemical performance test analysis of the positive electrode materials of the above embodiments and comparative examples is shown in the following table, and Figure 2 is a temperature-time relationship curve of Examples 3, 4, 5, 6 of the present invention and Comparative Example 2; Figure 3 1 is the XRD diagram of Examples 1 and 2 of the present invention and Comparative Example 1; Figure 4 is the XRD diagram of Examples 3, 4, 5, 6 of the present invention and Comparative Example 2; Figure 5 is the XRD diagram of Examples 7 and 8 of the present invention and Comparative Example 3; Figure 6 1 and 2 are XRD diagrams of Examples 9 and 10 of the present invention and Comparative Example 4.

[0070] Table 1 Electrochemical performance test structure of positive electrode materials of Example 1-Example 10 and Comparative Example 1-Comparative Example 4

[0071]

[0072]

[0073] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0074] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A linear cooling process for layered ternary cathode materials, characterized in that: The steps include: Step 1: Ni x Co y Mn z The (OH)2 hydroxide precursor is mixed with a lithium source by a high-efficiency mixer and then calcined at high temperature; Step 2, the material calcined in step 1 is linearly cooled from high temperature, and the temperature is lowered to below 150° C. to obtain the LiNi x Co y Mn z O2 layered ternary cathode material; Among them, 0.5≤x≤1, 0≤y≤0.5, 0≤z≤0.5, x+y+z=1.

2. The linear cooling process of a layered ternary cathode material according to claim 1, characterized in that: The lithium source in step 1 is selected from one or a combination of lithium hydroxide, lithium carbonate, lithium acetate and lithium nitrate.

3. The linear cooling process of a layered ternary cathode material according to claim 2, characterized in that: The high temperature calcination and sintering process in step 2 is specifically calcining at 500° C. for 4-6 hours and calcining at 720-950° C. for 12 hours.

4. The linear cooling process of a layered ternary cathode material according to claim 3, characterized in that: The linear cooling rate of step 2 is 1-20°C / min.

5. The linear cooling process of a layered ternary cathode material according to claim 4, characterized in that: The operation process of step 1 and step 2 is carried out in an atmosphere furnace.